How to make fluorescein strips - Gilbert Arinda; Simon Arunga (Community Eye Health Journal, 2018)
Fluorescein strips are an essential diagnostic tool in eye care. They are useful for performing a number of procedures, such as measuring intraocular pressure, assessing dry eye and detecting corneal abrasions. Unfortunately, this basic item is not commonly available in many resource-limited settings. Here we describe how we make fluorescein strips at Mbarara University and Regional Referral Hospital Eye Centre.